Концепт „Огонь” в философии „Живой Этики”: лексико-тематическая категоризация - Fedorushkov, Yury (Studia Rossica Posnaniensia, 2015)
This paper focuses on describing possible directions of research on so-called superior expressions in the field of cognitive semantics. It presents an analysis of the concept of fire, which is examined in the theosophical texts of “Living Ethics”. The aim of the paper is to prove that the lexicographical understanding of ‘fire’ (in certain Russian dictionaries) is not the same as the philosophical understanding of this concept (“Living Ethics”) since as far as the latter is concerned, the concept of fire rather refers to the domain of thought and the noosphere (in terms of Neo-Platonism) rather than to a physical phenomenon. This fact is confirmed by analyzing lexical-thematic categories that are specific to selected models of collocation, in which one of the parts contains the stem огон- (огн-).